TAHFIDZ LEARNING METHODS IN SHAPING ISLAMIC CHARACTER AT AL FATTAH ISLAMIC BOARDING SCHOOL SIDOARJO - Wildan Mahiru Amrullah; Eni Fariyatul Fahyuni (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
This article reviews the concept of tahfidz learning to form better characters. This study is motivated by the effective and good tahfidz learning but still the lack of akhalaqul karimah in the scope of education. The hadith also explains that adab is more important than knowledge. The approach of this research is to use qualitative research. The data source of this research was conducted at the Al-Fattah Sidoarjo Islamic Boarding School. data collection techniques are carried out by observation and interviews. The data collected was then analyzed qualitatively. The results showed that there is a very effective method, namely the muraja'ah method so that the students who memorize the Qur'an have a strong memory because they often repeat the recitations they have memorized, but there are still many memorizers of the Qur'an who lack manners for others and from their personal side, therefore the memorizers of the Qur'an must also have good character, which has been exemplified by the Prophet Muhammad Saw.